Delayed Hypoparathyroidism following Thyroidectomy, a Diagnostic Conundrum: A Report of Three Cases from Sri Lanka. (17th September 2020) - Wijewickrama, Piyumi Sachindra Alwis; Rajaratnam, Henry N.
Abstract : Introduction . Hypoparathyroidism, which is a common complication following total thyroidectomy can be transient in majority and permanent in 1.5% of the patients and usually occurs secondary to an inadvertent removal of parathyroid glands, mechanical or thermal injury or disruption of the vasculature. In some patients, it is observed that symptoms of hypocalcemia can occur for the first time several years after the surgery, which is known as "delayed hypoparathyroidism." We report three cases of delayed hypoparathyroidism from Sri Lanka, presenting several years after total thyroidectomy. Case Presentation. Case 1- a 60-year-old Sri Lankan woman who presented with symptomatic hypocalcemia for the first time, 30 years after total thyroidectomy for follicular thyroid carcinoma. Case 2- a 53-year-old Sri Lankan woman presenting with neuropsychiatric manifestations of hypocalcemia for the first time, 12 years after total thyroidectomy for papillary thyroid carcinoma. Case 3- a 49-year-old Sri Lankan woman developing symptoms of hypocalcemia for the first time, 11 years after completion of thyroidectomy for papillary thyroid carcinoma. All these patients were detected to have low parathyroid hormone levels, without an alternative etiology for hypoparathyroidism, hence leading to a diagnosis of delayed post-thyroidectomy hypoparathyroidism. Conclusion . Delayed hypoparathyroidism is a rare phenomenon, which is secondary to progressive atrophy of parathyroid glands and slowly progressive hypovascularization of parathyroids due to scar tissue retraction following thyroidectomy. The nonspecific nature of hypocalcemic symptoms and lack of continuous follow-up for a long time after thyroidectomy could contribute to a further delay in diagnosis. However, it is an important diagnosis to consider in any patient with a history of neck surgery presenting with hypocalcemia, irrespective of the time duration of surgery, as timely diagnosis and treatment can prevent long-term complications of hypocalcemia and improve the quality of life.